Analysis of Segmentation and Targeting Strategies Of 4-Star Hotel Consumers In Jakarta - Siregar, Raymond; Novi Cahayani; Wulan Sari; Diandra Vizara Santoso; Wurianisa Purnamisuri (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the segmentation and targeting strategies for 4-star hotel consumers in Jakarta by identifying homogeneous customer groups and selecting the most promising target market. Using a quantitative descriptive approach, data were collected through a Likert-scale questionnaire covering four marketing mix variables: Product, Price, Place, and Promotion. Hierarchical Cluster Analysis was applied to identify market segments, resulting in six distinct clusters, followed by Non-Hierarchical Cluster Analysis to determine the target market. The findings indicate that Cluster 1 is the most attractive segment, characterized by guests who prioritize cleanliness, quality service, and complete facilities, and who are responsive to digital promotions. In terms of the 4P marketing mix, 4-star hotels have successfully delivered high-quality services, offered competitive yet premium pricing, maintained strategic locations, and utilized social media and online travel agents for effective promotion. The study recommends value-based marketing strategies to enhance customer loyalty and capitalize on peak seasons. Limitations include the restricted geographic scope to Jakarta and a short data collection period of two weeks. Future research should expand to other regions and extend the data collection timeframe to obtain more comprehensive results.